Genome-wide association study identifies eight loci associated with blood pressure - Newton-Cheh, Christopher; Johnson, Toby; Gateva, Vesela; Tobin, Martin D; Coin, Lachlan; Zhao, Jing Hua; Zhang, Feng; Farrall, Martin; Tanaka, Toshiko; Wallace, Chris; Chambers, John C; Khaw, Kay-Tee; et al. (Nature genetics, 2009)
Christopher Newton-Cheh and colleagues report a genome-wide association study for blood pressure traits as part of the Global BPgen consortium. They report eight loci with replicated association to systolic and/or diastolic blood pressure, with each also showing association to hypertension. Elevated blood pressure is a common, heritable cause of cardiovascular disease worldwide. To date, identification of common genetic variants influencing blood pressure has proven challenging. We tested 2.5 million genotyped and imputed SNPs for association with systolic and diastolic blood pressure in 34,433 subjects of European ancestry from the Global BPgen consortium and followed up findings with direct genotyping ( N ≤ 71,225 European ancestry, N ≤ 12,889 Indian Asian ancestry) and in silico comparison (CHARGE consortium, N = 29,136). We identified association between systolic or diastolic blood pressure and common variants in eight regions near the CYP17A1 ( P = 7 × 10 −24 ), CYP1A2 ( P = 1 × 10 −23 ), FGF5 ( P = 1 × 10 −21 ), SH2B3 ( P = 3 × 10 −18 ), MTHFR ( P = 2 × 10 −13 ), c10orf107 ( P = 1 × 10 −9 ), ZNF652 ( P = 5 × 10 −9 ) and PLCD3 ( P = 1 × 10 −8 ) genes. All variants associated with continuous blood pressure were associated with dichotomous hypertension. These associations between common variants and blood pressure and hypertension offer mechanistic insights into the regulation of blood pressure and may point to novel targets for interventions to prevent cardiovascular disease.